2016
DOI: 10.1186/s13550-016-0166-y
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging of pre-invasive breast cancer with a combination of VHHs targeting CAIX and HER2 increases contrast and facilitates tumour characterization

Abstract: BackgroundOptical molecular imaging is an emerging novel technology with applications in the diagnosis of cancer and assistance in image-guided surgery. A high tumour-to-background (T/B) ratio is crucial for successful imaging, which strongly depends on tumour-specific probes that rapidly accumulate in the tumour, while non-bound probes are rapidly cleared. Here, using pre-invasive breast cancer as a model, we investigate whether the use of combinations of probes with different target specificities results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…Other studies have assessed carbonic anhydrase IX (CAIX) and HER2-CAIX targeting for optical imaging ( 21 ). Notably, the HER2-CAIX combination synergistically enhanced the T/B ratio and could also detect lung metastases ( 22 ). Additionally, 89 Zr-HER3 ( 23 ), 18 F-HER2 ( 24 ), and 68 Ga-NOTA-CD20 ( 25 ) nanobodies have demonstrated success in various tumor models.…”
Section: Nanobodies In Cancer Imagingmentioning
confidence: 99%
“…Other studies have assessed carbonic anhydrase IX (CAIX) and HER2-CAIX targeting for optical imaging ( 21 ). Notably, the HER2-CAIX combination synergistically enhanced the T/B ratio and could also detect lung metastases ( 22 ). Additionally, 89 Zr-HER3 ( 23 ), 18 F-HER2 ( 24 ), and 68 Ga-NOTA-CD20 ( 25 ) nanobodies have demonstrated success in various tumor models.…”
Section: Nanobodies In Cancer Imagingmentioning
confidence: 99%
“…Periplasmic produced biotinylated nanobodies were exploited for the functionalization of microbubbles to use as ultrasound contrast agent [76], for the diagnostic of H3N2 and swine influenza, and for the identification of ochratoxin A contaminations in cereals [77][78][79][80]. Periplasmic expression was also successfully exploited to produce nanobodies suitable for reacting with maleimide fluorophores [81], fusions between VHHs and nanoluciferase to use as bioluminescent immunoreagents [82], for recovering correct-folded nanobody-intein fusion proteins suitable for thioester reactions and finally for the fabrication of immunomicelles [83]. This expression route was also preferred for producing a hybrid molecule in which an anti-lysozyme nanobody was inserted into a solvent-exposed loop of β-lactamase [84].…”
Section: Bacterial Periplasmmentioning
confidence: 99%
“…In 2016, Kijanka et al ( 147 ) reported a combination of optical conjugations based on two different Nbs against two different breast tumor markers, for an improved tumor detection: Nb B9 against CAIX, which targets the peri-necrotic regions of tumors, and Nb 11A4 against HER2. This dual-spectral imaging strategy accomplishes successfully the optical molecular imaging of CAIX and HER2-positive DCIS xenografts in vivo , under conditions mimicking surgical settings.…”
Section: Molecular Imaging With Nbs For Early Stage Diagnosis Of Tumomentioning
confidence: 99%
“…This dual-spectral imaging strategy accomplishes successfully the optical molecular imaging of CAIX and HER2-positive DCIS xenografts in vivo , under conditions mimicking surgical settings. This strategy is assumed to facilitate a faster detection of tumor markers, and it is highly promising to utilize the dual-spectral imaging strategy for the early diagnosis, treatment program planning, and monitoring the treatment response ( 147 ).…”
Section: Molecular Imaging With Nbs For Early Stage Diagnosis Of Tumomentioning
confidence: 99%